The Role Of Digital Technologies In Professional Development And Professional Choice In The Process Of Professional Choice. - Saparniyazova Rakhima Makhsetbaevna (Periodica Journal, 2024)
This article analyzes the role of digital technologies in career development. My research shows that digital technologies are changing the professional context of the younger generation and the available opportunities for career support. The impact of digital technology on career choices depends in part on the interaction of technology with society. They can be seen as tools, shapers of society or as social practices. For individuals, digital technologies can be understood through six metaphors: (1) library, (2) media channel, (3) surveillance camera, (4) marketplace, (5) meeting place, and (6) arena. Opting for referrals is using them to provide information, automated interactions, or communications. The article concludes by noting that three main pedagogical positions (instrumental, relational or critical) can be oriented. Ideas and proposals for career development in the harmonization of various information technologies and in solving the opportunities and problems presented to young people in choosing their profession are reflected in this article. Determining the training needs of young people and being able to clearly see their abilities is the most urgent problem in directing them to the profession. The use of digital technologies to solve such problems makes the work of specialists much easier.
Keywords: Professional development; career guidance; digital technologies